3D Bumper Animation Design as a Visual Identity Media for Wanarata Fest in Karangmangu Village - Azam, Muhammad Fadhil; Astrida, Deuis Nur (Journal of Multimedia Trend and Technology, 2025)
Wanarata Fest is a cultural event held in Karangmangu Village with the aim of introducing the potential of local culture and wisdom to the wider community. To support the delivery of the village's identity and potential, visual media are needed that can create a strong and representative first impression. This research aims to design a 3D bumper animation as a visual identity for Wanarata Fest, showcasing the cultural elements and character of Karangmangu Village. The method used in this research is the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, and testing. During the design stage, the selection of visual elements such as gunungan wayang (wayang puppet mountains), kuda kepang (horse-drawn carriages), joglo houses, and teak trees was based on observations and interviews with village officials to represent local cultural identity. Testing was conducted using the User Acceptance Testing (UAT) method, involving the committee and village officials as respondents. The test results showed that the 3D bumper animation received very positive ratings and acceptance, with all assessment indicators falling within the "very appropriate" category. This demonstrates that the designed 3D bumper animation is capable of representing the visual identity of Wanarata Fest and is suitable for use as an opening media for the event, with the potential for reuse in future events. Thus, 3D bumper animation can be an effective visual media solution in supporting the image and identity of local culture-based events.